A New Hypothesis: The Behistun Inscription as Imperial Calendar. Issue 2 (3rd July 2019) - Kosmin, Paul J.
ABSTRACT: This article proposes a function for the dates in the Behistun inscription of Darius I: that alongside its telling of an authorised story of righteous accession it made possible, and perhaps even established, a calendar of historical commemoration. The article makes observations about DB's internal chronography – its synchronisation of the Persian and Babylonian calendars, the function of its single-year container for the battles' day-month dates, and the stability, panimperial distribution, and continued availability of this information; it establishes parallels for annual victory calendars in Mesopotamia and Judea; and it identifies good, if infrequent, testimony to an Achaemenid concern with the institution of anniversary celebrations and battle commemorations.